Effectiveness of Information Education and Communication on Menstrual Hygiene among Adolescent School Girls of Jumla District - Dahal, Anika; Acharya, Kamal Prasad (Journal of Nobel Medical College, 2019)
Background: Menstruation and menstrual practices are darkened by taboos and different societal as well as cultural restrictions, which results in lack of adequate knowledge in adolescents regarding the scientific facts of menstruation as well as healthy menstrual hygiene practices. The objective of the study was to find out the effectiveness of information, education and communication (IEC) on menstrual hygiene among adolescents of Jumla district. Materials and Methods: Quasi-experimental research design was used for the study. The samples were taken from government school, Shree Janta Secondary Technical school of Chandannath municipality of Jumla District. A total of 112 adolescents girls studying in class 9 and class 10 were selected by using non probability total enumerative sampling technique. Data was collected by using self administered questionnaire. Data analysis was done by descriptive and inferential statistics. Results: The study revealed that 8.9% of respondents had high knowledge during pre test which was significantly increased to 60.7% during post test and 27.7% of respondents had good practice during pre test which was significantly increased to 51.8% during post test. Conclusion: The present study concluded that adolescents lacked appropriate knowledge and practices about menstruation in the pre test which significantly increased in post test. Thus, structured health education program can significantly bring positive change in healthy menstrual hygiene practices.